Perlindungan Hukum Terhadap Penurunan Omset Penjualan UMKM di Pasar Tanah Abang - Eliya Anis; Sumriyah (JOURNAL SAINS STUDENT RESEARCH, 2023)
Offline merchants who experience a decline in turnover due to competition with online sales may face significant challenges. This research explores how legal protection is for Tanah Abang traders who have minimal visitors because the products they sell are unable to compete with e-commerce by offering cheaper prices. One of the aspects studied in this journal is related to default where traders do not fulfill tax payments. This research also discusses legal protection for traders with government solutions to emphasize e-commerce parties in regulating sales algorithms. Based on the results of this research, it provides insight into traders and the civil law academic community